Volviendo a Husserl. Reactualizando el contexto filosófico tradicional del “problema” fenomenológico del otro. La Monadología de Leibniz - Hopkins, Burt (2011)
“Back to Husserl: Reclaiming the Traditional Philosophical Context ofthe Phenomenological ‘Problem’ of the Other: Leibniz’s Monadology”. The internalmotivation that led Husserl to revise his early view of the pure Ego as empty ofessential content is traced to the end of explicating his reformulation of phenomenologyas the egology of the concrete transcendental Ego. The necessity ofrecasting transcendental phenomenology as a transcendental idealism that followsfrom this reformulation is presented and the appearance of transcendentalsolipsism of this idealism exposed as unfounded. That the ground of this exposureis Husserl’s phenomenological appropriation of Leibniz’s metaphysical insightsinto the problem of accounting for the plurality of monads, and, therefore, not theCartesian problem of the other mind, is presented as the key to reclaiming thetraditional philosophical context of the phenomenological problem of the other.